Pengaruh Gratifikasi Instan Aplikasi TikTok terhadap Perilaku Belajar Siswa - Shiddiq, Salman; Taufik, Muhammad (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2024)
This article discusses the influence of instant gratification generated from using the TikTok app on students' learning behavior. The background of this article is the increasing use of TikTok among teenagers in Indonesia, especially in the age range of 18-24 years. This study uses the Uses and Gratification theory to explain why students are interested and addicted to using TikTok, as well as how TikTok usage behavior can affect students' learning behavior. Using the library research method, the researcher explains the influence of TikTok on learning behavior from various reading sources. The results show that the instant gratification obtained from using TikTok has created a new culture that has an impact on student learning behavior, such as difficulty in concentrating for a long time and negative implications for student learning culture. This article concludes that excessive use of TikTok can have a negative impact on student learning behavior, so efforts are needed to regulate and control the use of the TikTok application among students. Abstrak Artikel ini membahas pengaruh gratifikasi instan yang dihasilkan dari penggunaan aplikasi TikTok terhadap perilaku belajar siswa. Latar belakang artikel ini adalah meningkatnya penggunaan aplikasi TikTok di kalangan remaja di Indonesia, khususnya pada rentang usia 18-24 tahun. Studi ini menggunakan teori Uses and Gratification untuk menjelaskan mengapa siswa tertarik dan kecanduan menggunakan TikTok, serta bagaimana perilaku penggunaan TikTok dapat memengaruhi perilaku belajar siswa. Dengan metode studi literatur (library research) peneliti menjelaskan pengaruh TikTok terhadap perilaku belajar dari beragam sumber bacaan. Hasil penelitian menunjukkan bahwa gratifikasi instan yang didapat dari penggunaan TikTok telah menciptakan budaya baru yang berdampak pada perilaku belajar siswa, seperti kesulitan untuk berkonsentrasi dalam waktu yang lama dan implikasi negatif terhadap budaya belajar mahasiswa. Artikel ini menyimpulkan bahwa penggunaan TikTok yang berlebihan dapat memberikan dampak negatif terhadap perilaku belajar siswa, sehingga diperlukan upaya untuk mengatur dan mengontrol penggunaan aplikasi TikTok di kalangan siswa.